Pembuatan Selai Lembaran Ubi Benggala (Manihot esculenta) dengan Variasi Konsentrasi Gula Aren - Melly Harya Kurniatillah; Yuni Selvianti Sari (Politeknik Negeri Lhokseumawe, 2026)
Fruit leather is a chewy, dehydrated fruit puree rolled into flat, flexible sheets. Generally, fruit leather uses granulated sugar, but in this study, palm sugar was used. This study aims to determine the appropriate concentration of palm sugar and the physical and chemical characteristics of sweet potato fruit leather. The method used was an experimental design with 4 treatments based on physical and chemical parameters, including elongation, organoleptic, and fiber content tests. The elongation test results showed the following: control: 0.007%, P1: 0.11%, P2: 0.05%, and P3: 0.22%, with the highest elasticity observed in P3, which used 95 g of palm sugar. The crude fiber content test results for each treatment were 0.58%, 0.55%, 0.60%, and 0.63%, respectively. Organoleptic scoring and hedonic tests indicated that the treatment most preferred by the panelists was treatment 2, which used a concentration of 90 g of palm sugar. The conclusion of this study is that the best sweet potato sheet jam with varying concentrations of palm sugar, as determined by physical and chemical tests, was treatment 2, which used 90 g of palm sugar.